1978
DOI: 10.1103/physrevlett.41.163
|View full text |Cite
|
Sign up to set email alerts
|

Charge-State Dependence of Electron Loss from H by Collisions with Heavy, Highly Stripped Ions

Abstract: Theoretical calculations, confirmed by experimental measurements, are used to obtain a new scaling rule for electron loss from a hydrogen atom in collision with a heavy, highly stripped ion" The calculations cover the energy range 50 to 5000 keV/amu and charge states q from 1 to 50. The experiments are in the range 108 to 1140 keV/amu and charge states 3 to 22. A simple analytic expression that describes the electron-loss cross section for 1 < q ^ 50 in the energy range 50 to 5000 keV/amu is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(28 citation statements)
references
References 18 publications
6
22
0
Order By: Relevance
“…The overall uncertainty resulting from these processes is small since (1) the fields and geometry of the recoil-ion detector assured total collection of the recoil ions, and the relative detection eSciencies for He+ and He + recoil ions impacting on the channelplate detector were measured in ancillary experiments; (2) using information from Ref. [23], combined with beam-line pressures, the charge-state impurity components of the beam were found to be negligibly small; and (3) no contamination from H2+ was expected since contamination of the high purity target gas by H2 could be inferred from the presence or absence of an H+ dissociation fragment, which was, in fact, not observed. Dissociation of any water vapor contamination would also lead to H+ production but not to H2+ production.…”
Section: Experimental Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The overall uncertainty resulting from these processes is small since (1) the fields and geometry of the recoil-ion detector assured total collection of the recoil ions, and the relative detection eSciencies for He+ and He + recoil ions impacting on the channelplate detector were measured in ancillary experiments; (2) using information from Ref. [23], combined with beam-line pressures, the charge-state impurity components of the beam were found to be negligibly small; and (3) no contamination from H2+ was expected since contamination of the high purity target gas by H2 could be inferred from the presence or absence of an H+ dissociation fragment, which was, in fact, not observed. Dissociation of any water vapor contamination would also lead to H+ production but not to H2+ production.…”
Section: Experimental Techniquementioning
confidence: 99%
“…They did not take into account, however, differences in projectile charge states, which drastically effect the onset of the high-velocity regime. It has been previously shown that the projectile charge is fully as important as the projectile velocity in single ionization [23]. In a Comment by Andersen et al [24], it was argued that the data of Heber et al [12] could be explained within the framework of the one-step shakeoff mechanism and the two-step TS-1 and TS-2 mechanisms, and that no new double-ionization mechanism was required.…”
Section: Introductionmentioning
confidence: 99%
“…For typical binding energies (which range from tens of electron volts up to many kilo-electron volts), v n,l is of the order of 10 10 cm/s and so is well above the particle velocities v employed in the various examples of experimental data shown earlier in this paper. The familiar Rutherford inelastic cross-section (Thomson 1912) for a projectile of atomic number Z in the regime where v ≤ v n.l can then be written in the form (Olson et al . 1978)…”
Section: Velocity and Energy In Scatteringmentioning
confidence: 99%
“…In 1978, Olson et al [3] provided a scaling rule based on electron loss by hydrogen atoms colliding with a wide variety of projectile ions. They not only provided absolute cross sections but also showed that the energy scaling ranged from no velocity dependence at "low" velocities to a v proj -2 behavior at "high" velocities, as expected from the Born formula.…”
Section: Introductionmentioning
confidence: 99%